Isolation and Identification of Some Intestinal Parasites Eggs, Cysts and Oocysts From two Species of Diptera: Calliphoridae in Baghdad - Hadi, Afkar M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study documented the role of blowfly Chrysomya  albiceps and Chrysomya megacephala  as carriers of 15 species of intestinal parasites eggs, cysts and Oocysts  as a primary effort of Iraq, by external and internal techniques: 10 species of different parasites were reported in this study that transmitted mechanically by Calliphoridae fly ,eight of them are nematode eggs (Ancylostoma duodenal, Ascaridia sp., Ascaris lumbricoides, Parascaris equirum, Strongyloides stericoralis , Strongylus sp., Trichostrongylus  sp. and Toxocara canis)and cysts of  two species of protozoa ( Entamoba sp.and  Iodomaba butschlii).  Internal technique by stained the fluid gut of flies with Zael Nelson stain, was applied for 257 fly, three species of nematode eggs (Ascaris lumriciodes, Strongyloides  stericoralis and Trichuris sp.); one species of cestode eggs (Taenia sp.)  and three species of protozoa Oocysts (Cryptosporidium parvum, C. muris, and Cyclospora cayetanensis), were showed internally. This variety of parasites referred to wide distribution of these flies in Baghdad that risk for public health